How do employees maintain their well-being during loneliness? The power of organizational nostalgia - Tatar, Berivan; Muceldili, Busra; Erdil, Oya (EMERALD GROUP PUBLISHING LTD, 2024)
PurposeThe spread of technology usage and the increasing popularity of network technology have formed a basis for alternative working systems as virtual teams and teleworking in the working environment. However, social relations have weakened in these working systems and loneliness has become a common emotion in the workplace. Hence, the concept of loneliness has attracted significant interest in recent years. Yet, despite this interest, research examining loneliness in the workplace is limited in the literature. This study aims to investigate the role of workplace loneliness on intrinsic motivation and the effect of intrinsic motivation on employee well-being through the moderating role of organizational nostalgia.Design/methodology/approachData were collected from 380 respondents working in different sectors. The hypotheses were tested by using structural equation modeling and PROCESS macro for SPSS.FindingsResults empirically showed that workplace loneliness negatively relates to intrinsic motivation, intrinsic motivation positively relates to employee well-being, intrinsic motivation mediates the link between workplace loneliness and employee well-being and organizational nostalgia moderates the link between workplace loneliness and intrinsic motivation. Furthermore, organizational nostalgia also moderates the indirect effect of workplace loneliness on employee well-being through intrinsic motivation.Originality/valueTo the best of the authors' knowledge, this study contributes to the existing literature on workplace loneliness by investigating underlying mechanisms and boundary conditions for loneliness in the workplace.
Keywords: Workplace loneliness; Loneliness; Nostalgia; Organizational nostalgia; Intrinsic motivation; Well-being; MODERATING ROLE; NEED; SATISFACTION; RESOURCES; IDENTITY; BELONG; LIFE; Business & Economics